Global trends in the development of digital entrepreneurship business models: a bibliometric analysis - Matiushenko, Oleksii; Tiutiunyk, Inna (Management and Entrepreneurship: Trends of Development, 2025)
This article explores the dynamics of publication activity in the field of business models of digital entrepreneurship based on the data from the Scopus database over the period 2011–2024. The purpose of the study is to identify patterns in the development of scientific research on digital entrepreneurship and the evolution of business models as reliable tools for promoting entrepreneurial projects in the context of digitalization and globalization. An integrated bibliometric approach was employed to analyze research outcomes and publication trends related to business models in digital entrepreneurship. The articles search and data analysis were conducted using the Scopus database and its analytical tools. Keyword co-occurrence networks and clustering of research areas were visualized using VOSviewer software. The article has identified the key trends in the development of research in this field, in particular a significant increase in publications since 2018, resulting from the rise of global e-commerce and the influence of digital technologies on entrepreneurial activity. The most highly cited publications have been reviewed, along with the top 10 scholars who have made significant contributions to the study of digital entrepreneurship business models. Additionally, the distribution of publications by country and funding source was analyzed, highlighting the major centers of scientific activity. Based on keyword clustering via VOSviewer, the main research directions have been outlined, including digital entrepreneurship, e-commerce, business modeling, and innovation. The results may serve as a valuable resource for identifying current trends and future directions in digital entrepreneurship research.JEL Classification: F41, M13, М21